2017
DOI: 10.2503/hortj.okd-010
|View full text |Cite
|
Sign up to set email alerts
|

Thinning and Bagging Treatments and the Growing Region Influence Anthocyanin Accumulation in Red-fleshed Apple Fruit

Abstract: In common apple cultivars with white flesh and red skin, it is known that fruit overload lowers fruit quality, and that skin anthocyanin concentrations are reduced by bagging treatment and warmer climatic conditions. In this study, the effects of these factors on anthocyanin accumulation in the flesh of red-fleshed apples were investigated using 'Geneva' and 'Pink Pearl' apple cultivars. Excess fruiting resulted in decreased anthocyanin concentration in the flesh and the titration acidity of the fruit in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…In addition, cooler climate conditions are advantageous for flesh coloration in 'Kurenainoyume' (Matsumoto et al, 2018b). Honda et al (2014Honda et al ( , 2017 also showed the effect of cooler temperature on the flesh red coloration in 'Pink Pearl'. The practical technique of fruit bagging treatment described in this study has been widely utilized by growers in Aomori Prefecture for several years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cooler climate conditions are advantageous for flesh coloration in 'Kurenainoyume' (Matsumoto et al, 2018b). Honda et al (2014Honda et al ( , 2017 also showed the effect of cooler temperature on the flesh red coloration in 'Pink Pearl'. The practical technique of fruit bagging treatment described in this study has been widely utilized by growers in Aomori Prefecture for several years.…”
Section: Discussionmentioning
confidence: 99%
“…2C and 4C), but the effect of light on the flesh may be smaller than the skin in both 'Goshogawara' and 'Kurenainoyume'. Honda et al (2017) also reported that sunlight irradiation partially promoted anthocyanin accumulation in the flesh of non-bagging 'Geneva' (type 1) and 'Pink Pearl' (type 2) apples compared with bagging treatment (corresponding to continuous-bagging in our study); although there were differences between the non-bagging control and continuous-bagging in both cultivars with being some year to year variations (Honda et al, 2017). Similarly, red coloration of the flesh of both 'Goshogawara' and 'Kurenainoyume' tended to be light-dependent, but the extent showed year to year variations that were less sensitive than the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamane and Shibayama (2006a) recommended the application of trunk girdling to improve the fruit skin red coloration in grapes, and reducing the crop load to concentrate the photosynthetic assimilates to each fruitlet as an important measure to improve the red coloration of the fruit. Honda et al (2017) demonstrated the effects of bagging, temperature, and crop load on flesh coloration in type 2 red-fleshed apple 'Pink Pearl'. However, except for the report by Honda et al (2017), there are no studies that have focused on commercially grown type 2 red-fleshed apple fruit like 'Kurenainoyume' and examined the effects of temperature, shading, defoliation, and crop load on flesh coloration.…”
Section: Introductionmentioning
confidence: 99%
“…Honda et al (2017) demonstrated the effects of bagging, temperature, and crop load on flesh coloration in type 2 red-fleshed apple 'Pink Pearl'. However, except for the report by Honda et al (2017), there are no studies that have focused on commercially grown type 2 red-fleshed apple fruit like 'Kurenainoyume' and examined the effects of temperature, shading, defoliation, and crop load on flesh coloration.…”
Section: Introductionmentioning
confidence: 99%